2017
DOI: 10.1063/1.4990828
|View full text |Cite
|
Sign up to set email alerts
|

SERS active self-assembled diphenylalanine micro/nanostructures: A combined experimental and theoretical investigation

Abstract: Enhancing Raman signatures of molecules by self-assembled metal nanoparticles, nanolithography patterning, or by designing plasmonic nanostructures is widely used for detection of low abundance biological systems. Self-assembled peptide nanostructures provide a natural template for tethering Au and Ag nanoparticles due to its fractal surface. Here, we show the use of L,L-diphenylalanine micro-nanostructures (FF-MNSs) for the organization of Ag and Au nanoparticles (Nps) and its potential as surface-enhanced Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Despite the fact that many substrate designs have been developed to increase Raman intensity, there are very few studies in the literature that have used FF-PNTs as a template to support SERS active substrates 49 51 . It has been previously reported that aligned FF-PNT templates formed with plasmon-active Ag NPs enabled SERS detection of molecules 49 , 50 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that many substrate designs have been developed to increase Raman intensity, there are very few studies in the literature that have used FF-PNTs as a template to support SERS active substrates 49 51 . It has been previously reported that aligned FF-PNT templates formed with plasmon-active Ag NPs enabled SERS detection of molecules 49 , 50 .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the interest of FF nanostructures as potential surface-enhanced Raman spectroscopy (SERS) substrates for biosensing and biomedical applications was demonstrated via TEM, Raman, luminescence and DFT calculations [ 121 ]. At 150 °C, L,L–FF micro-nanostructures (FF-MNSs) are subjected to an irreversible phase transition from hexagonally packed (hex) micro-nanotubes to an orthorhombic (ort) structure.…”
Section: Physico-chemical Characterization Of Short Peptides and Their Assemblymentioning
confidence: 99%
“…One of the strategies to combat biofouling is to design a surface that will resist bacterial adhesion . This includes hydrophobic and hydrophilic polymer‐based materials, zwitterionic compounds, and topographical modification of the surface .…”
Section: Introductionmentioning
confidence: 99%